A STUDY ON THE POLYMORPHIC FOURTH CHROMOSOME OF CHIRONOMUS STRIATIPENNIS (KIEFFER) - P. SARKAR,; S. BHADURI,; C. GHOSH,; T. MIDYA, (The Bioscan, 2011)
Chironomus striatipennis(Kieffer) contains four well organized polytene chromosomes in a salivary gland cell of the fourth instar larva. Out of the four chromosomes the fourth one is acrocentric and smallest in size.The fourth chromosome in this species showed various polymorphic organizations in the specimens collected from different habitats with differential heavy metal concentrations suggesting a differential response of this chromosome under different conditions. The polymorphic organizations also indicated the presence of some weak zones at several regions of the chromosome those may promote differential organization of the chromosome in this species.